Health consequences of thick forest fire smoke to healthy residents in Riau, Indonesia: a cross-sectional study (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Indonesia forest fire in 2015 emitted a huge amount of pollutants into the air. This study was aimed to assess the health consequences of forest fire smoke in healthy residents in Riau during forest fire disaster in 2015. METHODS This cross-sectional study was performed in healthy residents who lived in Pekanbaru, Riau Province, Sumatera, for at least 6 months during forest fire disaster in 2015, and data were taken in October 2015. Questionnaires consisting of respiratory and non-respiratory symptoms were collected. Lung function was assessed by spirometry (MIR II Spirolab™ spirometer, Medical International Research, Italy) and exhaled carbon monoxide (CO) was assessed using piCO+ Smokerlyzer®. Heart rate at rest and oxygen saturation in the room air were measured using Onyx 9591 Pulse Oximeter®. RESULTS A total of 89 subjects were mostly female (75.3%), housewife (37.7%), nonsmoker (86.5%) with mean age of 38.9 years old. The non-respiratory and respiratory symptoms were reported in 84.7% and 71.4% subjects, respectively. Lung function was impaired in 72.6% subjects, mostly with mild obstruction and mild restriction. Exhaled CO was highly detected over normal values (mean [standard deviation] = 32.6 [9.97] ppm) with predicted carboxyhemoglobin (COHb) of 5.74 (1.56). CONCLUSIONS Forest fire smoke exposure increased the respiratory and nonrespiratory symptoms among healthy individuals, which showed impairment in lung function, exhaled CO, and predicted COHb. Long term health effects on healthy individuals exposed to forest fire smoke warrant further evaluation.